Postures et mises en scène de la presse satirique dans l’espace public francophone d’Afrique subsaharienne - Jean Pierre Sagno (Communication)
The author explains how the forms of expression used by satirical press help create a public arena in French-speaking sub-Saharan Africa, a process that plays a role in democracy building. The author bases his work on different materials from a variety of sources: a summary of works on the public arena and on news satirists in French-speaking Africa, press articles and videos about news satirists in an African context, accounts of the role of news satirists in democracy building and the challenges and/or constraints that keep it from flourishing, and articles about conflicts and disagreements with the reigning political powers.